Memory and understanding : concept formation in Proust's A la recherche du temps perdu - Bartsch, Renate, 1939- (Amsterdam ; Philadelphia : J. Benjamins, 2005)
This book treats memory and understanding on two levels, on the phenomenological level of experience, on which a theory of dynamic conceptual semantics is built, and on the neuro-connectionist level, which supports the capacities of concept formation, remembering, and understanding. A neuro-connectionist circuit architecture of a constructive memory is developed in which understanding and remembering are modelled in accordance with the constituent structures of a dynamic conceptual semantics. Consciousness emerges by circuit activation between conceptual indicators and episodic indices with th.
Memory and Understanding; Editorial page; Title page; LCC data; Table of contents; Preface; 1. Introduction; 2. Memory; 3. Concept formation, remembrance, and understanding; 4. Epilogue; References; Index; The series Advances in Consciousness Research.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Proust, Marcel, -- 1871-1922.; Proust, Marcel, -- 1871-1922.; À la recherche du temps perdu (Proust, Marcel); Memory in literature; Memory; Concept Formation; Comprehension; Literature, Modern; Memory; Mémoire dans la littérature.; Mémoire.; memory (psychological concept); PSYCHOLOGY; Cognitive Psychology & Cognition; LITERARY CRITICISM -- European -- French; Memory; Memory in literature; À la recherche du temps perdu (Proust); Geheugen; Letterkunde; French Literature; Romance Literatures; Languages & Literatures